Respuesta :
Answer:
Option C) f(–3) and f(–2.1)
Step-by-step explanation:
We are given the following information in the question:
[tex]f(x) = y = [x] - 1[/tex]
where [x] is the greatest integer function.
A) f(–1) and f(–2)
[tex]f(-1) = [-1] - 1 = -1-1 = -2\\f(-2) = [-2] - 1 = -2-1 = -3[/tex]
The two functions are not equivalent.
B) f(1) and f(0)
[tex]f(1) = [1] - 1 = 1-1 = 0\\f(0) = [0] - 1 = 0-1 = -1[/tex]
The two functions are not equivalent.
C) f(–3) and f(–2.1)
[tex]f(-3) = [-3] - 1 = -3-1 = -4\\f(-2.1) = [-2.1] - 1 = -3-1 = -4[/tex]
The two functions are equivalent.
D) f(2) and f(1.9)
[tex]f(2) = [2] - 1 = 2-1 = 1\\f(1.9) = [1.9] - 1 = 1-1 = 0[/tex]
The two functions are not equivalent.